MUSIC EDUCATION AND TASTE FORMING OF CLASSICAL MUSIC STYLE: CASE STUDY IN CULTURAL INSTITUTIONKARTA PUSTAKA YOGYAKARTA INDONESIA - Sitowati, Inggit (Harmonia: Journal of Arts Research and Education, 2014)
Karta Pustaka is one of the cultural institutions in Yogyakarta, which has a classical music concert program. The purpose of this study is to describe the history of Karta Pustaka and organizing classical music concerts, the concert format, and its role in supporting classical music education in Yogyakarta. The method used in this study is qualitative research with historical and musicological approach.The data are collected by using interviews, documents and observations. Data were analyzed using qualitative descriptions technicians. The results showed that Karta Pustaka as cultural institution has become a classical musicmedia which has a supporting role in classical music education in Yogyakarta. The classical music concert program and classical music workshop held by Karta Pustaka information and knowledge for the students and people of musical art in Yogyakarta. In addition Karta Pustaka also acts as a forming media and the development of consumerâs classical music tastes and styles in Yogyakarta.